2013
DOI: 10.1158/1078-0432.ccr-12-3690
|View full text |Cite
|
Sign up to set email alerts
|

A Poor Prognosis Subtype of HNSCC Is Consistently Observed across Methylome, Transcriptome, and miRNome Analysis

Abstract: Purpose: Distant metastasis after treatment is observed in about 20% of squamous cell carcinoma of the head and neck (HNSCC). In the absence of any validated robust biomarker, patients at higher risk for metastasis cannot be provided with tailored therapy. To identify prognostic HNSCC molecular subgroups and potential biomarkers, we have conducted genome-wide integrated analysis of four omic sets of data.Experimental Design: Using state-of-the-art technologies, a core set of 45 metastasizing and 55 nonmetastas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 50 publications
(55 reference statements)
2
43
0
Order By: Relevance
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the complementarity among the various "omes" of HNSCC appears to offer an unparalleled opportunity for integration to achieve improved patient classification. In fact, a recent study has demonstrated the exquisite prognostic utility of 3p loss and TP53 mutations to classify HNSCCs (56,57). Underrepresentation of oropharyngeal cancers, particularly HPV þ tumors, is one potential caveat of these molecular investigations.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…We previously showed that the "R1" cluster of patient was characterized by alterations of pathways involved in EMT [6]. In accordance, a significant reduction of E-cadherin expression and an increase of the vimentin/E-cadherin ratio were found in "R1" patients compared to "non-R"1 tumours.…”
Section: Impactjournalscom/oncotargetmentioning
confidence: 57%
“…The way tumor cells interact with and modify their environment is a key issue in the acquisition of metastatic properties. In accordance, "R1" tumors are characterized by alterations of pathways involved in cell-cell adhesion, extracellular matrix (ECM), epithelial-to-mesenchymal transition (EMT), immune response and apoptosis [6]. Similarly, alterations of genes controlling adhesion, motility and invasiveness especially integrins were reported as the major molecular differences among metastatic and nonmetastatic HNSCC tumors [7][8][9].…”
Section: Introductionmentioning
confidence: 96%